Удосконалення цивільно-правового регулювання природних прав людини на життя та на репродуктивне відтворення - Чечерський, Віктор Іванович; Чечерський, В. І.; Checherskiy, Viktor (ВД "Гельветика", 2020)
Незважаючи на велику практику застосування репродуктивних технологій, на законодавчому рівні до теперішнього часу не вирішено навіть питання про те, яке місце займає право людини на репродукцію і продовження роду серед інших прав людини. У статті проаналізовано точки зору на це питання, які висловлені в юридичній літературі, у тому числі з позиції цивільного права. Зроблено висновок, що право на репродуктивне відтворення – це самостійне фундаментальне право людини, яке не є складовою права на життя, а чинна редакція статті 281 ЦК України не відповідає сучасним вимогам. Запропоновано зміни до цього Кодексу з метою належного врегулювання згаданих природних прав людини.

The regulatory environment lags behind developing social relations is quite natural. However, the lag of legal regulation in the reproductive sphere has become excessive. Despite the extensive practice of using reproductive technologies, even the question of what place the human right to reproduction and procreation occupies among other human rights has not yet been resolved at the legislative level. It is argued that the right to reproductive procreation, although interconnected with the right to life, has its own object and subject of regulation, and their content is not identical. In some cases, the right to life and the right to reproductive reproduction may be in antagonistic opposition to each other. In this regard, the observance of one of these rights will violate the other. Moreover, there is a difference in the basis on which these natural rights are based. While in the human right to life, first of all, the basis is the innate need for survival (self-preservation), then in the right for reproductive procreation is the innate need for procreation. It is indicated that the Civil Code of Ukraine, in comparison with other legislative acts, significantly limited the grounds under which assisted reproductive technologies can be applied. The article analyzes the approaches to solving this issue expressed in the legal literature. The approaches to solving the problem from the standpoint of civil law are analyzed. It is concluded that the right to reproductive procreation is an independent fundamental human right which is not a composite right to life, and the current version of Article 281 of the Civil Code of Ukraine does not meet modern requirements. It is proved that an individual has an inalienable right to reproductive procreation, which consists in the free and responsible decision-making on the birth of genetically native children, their number and duration between their birth or refusal to exercise this right. Changes to Civil Code of Ukraine are proposed with a view to the proper settlement of the mentioned natural human rights. Supplement the Code with article 281-1 “Right to Reproductive procreation” which, inter alia, regulates sterilization, the right to use assisted reproductive technologies, the right to abortion, and human cloning too.
Чечерський В. І. Удосконалення цивільно-правового регулювання природних прав людини на життя та на репродуктивне відтворення / В. І. Чечерський // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 25-29.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; права людини; природні права; право на репродуктивне відтворення; репродуктивні права; право на життя; human rights; natural rights; right to reproductive procreation; reproductive rights; the right to life